Pro NetBeans™ IDE 5.5 Enterprise Edition - Myatt, Adam (Apress, 2012)
This book explores the many features of NetBeans IDE 5.5. Developers can focus on a variety of technologies and areas when learning NetBeans. With the latest release, developers have access to an impressive array of features for working with JavaServer Faces (JSF), Ajax, Unified Modeling Language (UML) modeling, Enterprise JavaBeans (EJB 3.0), the Java Persistence API, web services, Business Process Execution Language (BPEL), and more. I wanted to write a book that really showcased the fantastic tools for working with these technologies.HTTP